Response surface optimisation for highly efficient removal of 17α-ethinylestradiol by novel kenaf core modification in aqueous solution - Nasir, H. M.; Aris, A. Z.; Abdullah, L. C.; Ismail, I. (Springer, 2022)
This research aims to ascertain the optimum conditions and interaction effects of selected variables via response surface methodology incorporated with central composite design in a batch treatment system. A quadratic model was obtained through the influence effects of the selected variables. Four variables pH (A), initial concentration (B), contact time (C), and biosorbent dosage (D), were selected to obtain high efficiency in the removal of the steroid hormone 17α-ethinylestradiol using modified kenaf core. The biosorbent characterisation, which was modified via chemical acid activation, was investigated through surface morphology structures using field emission scanning electron microscopy, Brunauer–Emmett–Teller, and fourier transform infrared spectroscopy analyses. The optimum conditions in an aqueous solution, obtained through a verification optimisation process, are 5.9, 28.2 mg/L, 216 min, and 0.40 g for variables A, B, C, and D, respectively. The pH and initial concentration explain the most significant interaction effect (F-value 23.12) at pH 4.6–5.8, with the lowest initial concentration being a good sign for the application of modified kenaf core in the real environment. The optimum removal rate computed in the quadratic model was 100. In comparison, the real experimental set-up achieved a 99.3 17α-ethinylestradiol removal rate, which is in great agreement with the predicted rate with a small percentage error (0.7) between the experimental and predicted values. Linear regression provided a best-fit isotherm with the Langmuir model. The results prove that modified kenaf core has enormous potential for 17α-ethinylestradiol removal due to its excellent surface morphological structure and high removal efficiency.